High Mountain Environment Project, 1968 Field Season - Marcus, Melvin G. (ARCTIC, 1969)
Under sponsorship of the U.S. Army Research Office, Durham, the Arctic Institute's High Mountain Environment Project continued research activities for the second year in the St. Elias and Wrangell Mountains, Yukon and Alaska. Twenty-three investigators and their assistants maintained a three-phase program from May to August 1968. .